Progesterone Receptor–Mediated Actions Regulate Remodeling of the Cervix in Preparation for Preterm Parturition. (November 2016) - Kirby, Michael A.; Heuerman, Anne C.; Custer, Melisa; Dobyns, Abigail E.; Strilaeff, Ryan; Stutz, Kathleen N.; Cooperrider, Jaclyn; Elsissy, Joseph G.; Yellon, Steven M.
This study determined whether a progesterone (P) receptor (PR)-mediated mechanism regulates morphological characteristics associated with prepartum cervix remodeling at term and with preterm birth. With focus on the transition from a soft to ripe cervix, the cervix stroma of untreated controls had reduced cell nuclei density/area and less organized extracellular collagen, while the density of macrophages/area, but not neutrophils, increased just 2 days before birth (day 17 vs day 15 or 16.5 postbreeding). Preterm birth was induced within 24 hours of treatment on day 16 postbreeding with PR antagonist or ovariectomy (Ovx). Pure or mixed PR antagonists increased the density of macrophages in the cervix within 8 hours (day 16.5 postbreeding), in advance of preterm birth. However, neither PR antagonists nor P withdrawal after Ovx affected the densities of cell nuclei and neutrophils or extracellular collagen compared to the same day controls—an indication that the cervix was sufficiently remodeled for birth to occur. To block the effect of systemic P withdrawal, Ovx pregnant mice were given a PR agonist, either pure or mixed. These treatments forestalled preterm birth and prevented further morphological remodeling of the cervix. The resulting increase in macrophage density in cervix stroma following Ovx was only blocked by a pure PR agonist. These findings support the hypothesis that inflammatory processes in the prepartum cervix that include residency of macrophages, cellular hypertrophy, and extracellular collagen structure are regulated by genomic actions of PR in a final common mechanism both at term and with induced preterm birth.